Trocar Puncture With a Sump Drain for Crohn's Disease With Intra-Abdominal Abscess: A 10-Year Retrospective Cohort Study - Juanhan Liu; Wenbin Gong; Peizhao Liu; Yangguang Li; Tao Zheng; Zhiwu Hong; Huajian Ren; Guosheng Gu; Gefei Wang; Xiuwen Wu; Xiuwen Wu; Xiuwen Wu; et al. (Frontiers in Surgery, 2022)
BackgroundTraditional percutaneous catheter drainage (PCD) and surgical intervention could not always achieve satisfactory results for patients with Crohn's disease (CD) who have complications with intra-abdominal abscess. We proposed a trocar puncture with sump drainage for the treatment of CD with intra-abdominal abscess and compared it with the conventional PCD and surgical intervention.MethodsCrohn's disease patients with intra-abdominal abscess and admitted to our hospital from 2011 to 2020 were identified by reviewing the electronic medical records. We divided them into Trocar, PCD, and fecal diverting (FD) groups, according to the ways of treating an abscess. Outcomes, risk factors for abscess recurrence, and postoperative complications were compared among the three groups.ResultsA total of 69 patients were included and they were divided into Trocar (n = 18), PCD (n = 29), and FD (n = 22) groups. Four patients in the PCD group were transferred to receive the FD surgery due to the failure of initial treatment. The incidence of abscess recurrence was significantly higher in the PCD (48%) and FD (50%) groups compared to the patients using the trocar puncture with the sump drain (Trocar group) (16.7%). There were 8 patients in Trocar, 22 in PCD, and 20 s in the FD group who received enterectomy. None of the patients in the Trocar had an ultimate stoma and the incidence of postoperative complications was statistically lower [0% (Trocar) vs. 31.8% (PCD) vs. 45% (FD), P < 0.05]. The way of initial treating of the abscess was significantly correlated with the abscess recurrence and postoperative complications.ConclusionsTrocar puncture with a sump drain had a lower incidence of abscess recurrence, abdominal adhesions, postdrainage, and postoperative complications compared to the conventional PCD or surgical intervention.